Protective Effects of Memantine in Experimentally Induced Cerebral Ischemia and Reperfusion Injury in Rats - Ozdemir, Hasan Hueyin; Demir, Caner F.; Berilgen, M. Said; Akgun, Bekir; Kuloglu, Tuncay; Kapan, Oktay; Balduz, Metin (Turkish Neurological Soc, 2013)
Objective: The severity of apoptosis developing after hypoxia-ischemia and reperfusion is an indicator of cerebral injury. In cerebral ischemia, there are many factors initiating the events progressing to cell death. The most common leading cause is excessive increase in intracellular calcium concentration. Ion channels in NMDA receptors cause cell death by increasing Ca++ entries into the cell. Memantine is a non-competitive excitatory amino acid blocker of the NMDA receptor. Studies suggesting administration of memantine before and after ischemia decreasing the neural injury have been published. In this study we aimed to examine the memantine could have a decreasing effect on neuronal injury resulting with apoptosis especially in the penumbra region after ischemia and its effects on antioxidants and oxidants in brain tissues. Material and Met-hod: Experimental study was performed in three groups; each of them including 7 rats. The control group (without any intervention) was used for evaluation of the normal brain tissue. Transient focal cerebral ischemia was performed by clipping the right common carotid arteries of the rats in ischemia and ischemia-drug groups. Ten mg/kg intraperitoneal memantine was administered in ischemia-drug group 30 minutes after ischemia and for 5 days thereafter. All of the rats were sacrificed after the experiment. Antioxidant and oxidant levels of the cerebral tissues were measured. Apoptotic cells were determined immunohistochemically using TUNEL method. Results: When the memantine administered group was compared with the ischemia group, we observed that memantine decreased apoptotic cells in the brain tissue and there was an improvement in the oxidant levels (p< 0.05). Discussion: In conclusion, memantine may be effective in prevention of apopitosis and neuronal injury in cerebral ischemic tissue via decreasing cerebral oxidant formations.
Keywords: Memantine; apoptosis; ischemic stroke; antioxidants; oxidants